If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lnx + ln(x + 6) = ln Reorder the terms: lnx + ln(6 + x) = ln lnx + (6 * ln + x * ln) = ln lnx + (6ln + lnx) = ln Reorder the terms: 6ln + lnx + lnx = ln Combine like terms: lnx + lnx = 2lnx 6ln + 2lnx = ln Solving 6ln + 2lnx = ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1ln' to each side of the equation. 6ln + -1ln + 2lnx = ln + -1ln Combine like terms: 6ln + -1ln = 5ln 5ln + 2lnx = ln + -1ln Combine like terms: ln + -1ln = 0 5ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(5 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Add '-2x' to each side of the equation. 2x + -2x = -5 + -2x Combine like terms: 2x + -2x = 0 0 = -5 + -2x Simplifying 0 = -5 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 8p+2=4(2p-1) | | 2x+306,000=3306000 | | -3t^2+36t=0 | | -5x^3+6x^2-5x-2=0 | | x^3+3x=19 | | 81t-36=144t-36 | | =9+5(t+1)+4t | | x+306,000=3306000 | | 8xX=8 | | =7(t+9)+5+t | | 5c-5=90 | | h(t)=-t^2+6t | | y=4x^2-8x-5 | | 7(x-8)-4(1-2x)=x+4+x+1 | | =8t+(7+3t)4+2t | | -2x+-98=2 | | -5x+13=3x+18 | | -16-6x=-2(8x-7) | | 3x-3y=10 | | 2(3-4d)=-42 | | -4(4y-10)+3(3y+10)= | | 2(5-x)=-25 | | 4(z-20)=16 | | =4t+9+(2t+7)6 | | 5x+x=222 | | 9b+6=30 | | 2(g-4)=6 | | =6t+3(2+9t)+7 | | x+9+5x=21x+2x | | y=-5+3x-2x^2 | | -6k+2k+10=-2(k-3)+4 | | 3/4(m)=-5/6 |